UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI PENERAPAN METODE LATIHAN SISWA KELAS II SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Sri Heruwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research was motivated by low yields social studies class II SD Negeri 010 Banjar Panjang Kecamatan Kerumutan. Of the 20 students hanya10 students (50.00%), which reached the KKM. The purpose of this study is to improve learning outcomes IPS through the implementation of training methods. This research is a class act, carried out by two cycles. Data of this research focuses on improving mastery learning and student learning outcomes IPS. Results of the study revealed that after the implementation of training methods hasl learning and increased student learning completeness. On the preliminary data the number of students who completed is 10 students (50%) have increased in the first cycle by the number of students 14 students (70%) and an increase in the second cycle by the number of students 16 students (80%). Besides learning outcomes IPS sisaw also increased. In preliminary data the average value of students is 55. In the first cycle increased to 60 and the second cycle increased with an average value of 64.